Sustainable production of a new generation biofuel by lipase-catalyzed esterification of fatty acids from liquid industrial waste biomass. (August 2017) - Foukis, Athanasios; Gkini, Olga A.; Stergiou, Panagiota-Yiolanda; Sakkas, Vasilios A.; Dima, Agapi; Boura, Konstantina; Koutinas, Athanasios; Papamichael, Emmanuel M.
Graphical abstract: Highlights: Lipase-catalyzed esterification of fatty acids from industrial wastes' acidogenesis. Production of a new generation biofuel at very high yield and concentration. Optimal reaction conditions were achieved by factorial central composite designs. CALB was significantly stable and recovered after ten cycles of esterification. Abstract: In this work we suggest a methodology comprising the design and use of cost-effective, sustainable, and environmentally friendly process for biofuel production compatible with the market demands. A new generation biofuel is produced using fatty acids, which were generated from acidogenesis of industrial wastes of bioethanol distilleries, and esterified with selected alcohols by immobilized Candida antarctica Lipase-B. Suitable reactors with significant parameters and conditions were studied through experimental design, and novel esterification processes were suggested; among others, the continuous removal of the produced water was provided. Finally, economically sustainable biofuel production was achieved providing high ester yield (<97%) along with augmented concentration (3.35 M) in the reaction mixtures at relatively short esterification times, whereas the immobilized lipase maintained over 90% of its initial esterifying ability after reused for ten cycles.